Caracterização Físico-química de Cerveja produzida em uma Micro Cervejaria da Região de Guarapuava - PR - Kutkoski, Rafael Francisco (2018)
This work presents a physicochemical characterization of beers produced in a micro brewery in the region of Guarapuava – PR, with the purpose to contribute to the standardization of the productive process and the quality control of the beverage produced, with physicochemical analysis such as pH, acidity, bitterness, color, alcoholic content and 5-hydroxymethil-2-furaldehyde (HMF) content, realized in samples collected at the end of the main stages of the production (mashing, boiling, fermentation, maturation) statistically analyzed. In addition, a validation study of the HPLC-UV method and quantification of the HMF compound in the lager beer samples was also performed. The results obtained with the application of statistical calculations indicate significant differences in all stages of the beer production process in the nine samples collected. The factors that influenced this difference were the alkalinity of the water utilized in the production, changes in the raw material lot and changes in the formulation. The evaluation of the parameters in the stage of maturation (finished beer) shows an adequate physicochemical quality according to standards cited in the literature for the style of lager beer. For the validation of HMF determination, the results indicated adequate precision values (RSD for repeatability and intermediate precision of 1.39% and 8.58%, respectively) and accuracy (recovery rates between 96 - 110%) according to literature recommendations. The limits of detection (LD) and quantification (LQ) of 0.112 and 0.372 mg L-1, respectively, were low, demonstrating the sensitivity of the HPLC-UV method for determination of this contaminant. A good linearity was also observed in the concentration range of 0.5 to 8.0 mg L-1, with Fregression values = 13154.45 > Fcritic = 6.55 and without adjustment of the linear model ((Ffaj =2.21 < Fcritic = 5.08; p>0.05)). In addition, comparison of HMF standard chromatograms and sample chromatograms indicates that the method shows good selectivity. Therefore, the validation study performed in this work indicated that the chromatographic methodology was adequate for the quantification of HMF in beer.